Geochemical and geotechnical characterization of soils developed on volcanic rocks on the Bamenda mountain (Cameroon volcanic line) - Dongmo A, Kagou; C .S, Guedjeo; A.T, Primus; P, Wotchoko; M.L, Chenyui; B.T, Aziwo; K.V, Kamgang (International Journal of Advanced Geosciences, 2018)
The weathering mechanism of rocks exposed under the same conditions on the Bamenda Mountain is not well understood. The aim of this study is to characterize basalt, trachyte and rhyolite and their products on the geochemical and geotechnical aspect. Here three wells were hand dug on rocks developed on basalt, trachyte and rhyolite and studied. The results showed that, Ki values (0.34-6.57) indicate SiO2 are more leached on soils developed on basalt than those on trachyte and rhyolite. CIA (72.62-97.8) and CIW (72.76-98.8) indicate an advanced to extreme chemical weathering in this environment, with rhyolite and trachyte more weathered than basalts. Soils formed on basalt have ICV >1 signifying they are young and immature, while those on trachyte and rhyolite ICV =0.3-0.5 indicate intense chemical weathering. Al (EFAl=1.5) and Fe (EFFe=1.3) are enriched in the soils and while SiO2, Na, K, Ca and Mg are depleted in the soils profile as one moves upward. Geotechnically, these soils are predominantly silts, well graded, less plastic (LI<0), plastic (CI>1) to moderately plastic (PI=7.2-15.8). Soils developed on rhyolite have high clay content MBV= 3.3-8, but low water content (10-42%). Texturally, these soil are silty loam, loam to sandy loam soils. Soil strength of the soils is low: cohesion (<0.5bar), angle of internal friction (10-43Â°), with shallow landslides (1-2m) more likely to occur on trachyte and on rhyolites.Â Â Â